2008
DOI: 10.1086/527527
|View full text |Cite
|
Sign up to set email alerts
|

Injection and Interplanetary Transport of Near‐Relativistic Electrons: Modeling the Impulsive Event on 2000 May 1

Abstract: We present a Monte Carlo method to model the transport of solar near-relativistic electrons in the interplanetary medium, including adiabatic focusing, pitch-angle dependent scattering, and solar wind effects. By taking into account the angular response of the LEFS60 telescope of the EPAM instrument on board the ACE spacecraft, we transform the simulated pitch-angle distributions into the sectored intensities measured by the telescope. The goal is to deconvolve the effects of the interplanetary transport in or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
84
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(84 citation statements)
references
References 43 publications
0
84
0
Order By: Relevance
“…SEPServer 1 currently hosts a database of results of a Monte Carlo interplanetary transport model (Agueda et al, 2008) to aid the study of near-relativistic (>50 keV) electron events observed by STEREO/SEPT (Agueda et al, 2012). The transport model solves the focused transport equation (Roelof, 1969;Ruffolo, 1995), including the effects of particle streaming along the magnetic field lines, adiabatic focusing by the diverging magnetic field (Roelof, 1969), interplanetary scattering by magnetic fluctuations frozen into the solar wind (Jokipii, 1966;Dröge, 2003), convection with scattering fluctuations, and adiabatic deceleration resulting from the interplay of scattering and focusing (Ruffolo, 1995;Kocharov et al, 1998).…”
Section: Modelingmentioning
confidence: 99%
“…SEPServer 1 currently hosts a database of results of a Monte Carlo interplanetary transport model (Agueda et al, 2008) to aid the study of near-relativistic (>50 keV) electron events observed by STEREO/SEPT (Agueda et al, 2012). The transport model solves the focused transport equation (Roelof, 1969;Ruffolo, 1995), including the effects of particle streaming along the magnetic field lines, adiabatic focusing by the diverging magnetic field (Roelof, 1969), interplanetary scattering by magnetic fluctuations frozen into the solar wind (Jokipii, 1966;Dröge, 2003), convection with scattering fluctuations, and adiabatic deceleration resulting from the interplay of scattering and focusing (Ruffolo, 1995;Kocharov et al, 1998).…”
Section: Modelingmentioning
confidence: 99%
“…We simulate the interplanetary transport of SEPs injected at the root of an Archimedean spiral magnetic field line using the Monte Carlo technique (Agueda et al 2008). The model includes particle streaming along the magnetic field lines, pitch-angle focusing by the diverging IMF, pitch-angle scattering by magnetic fluctuations, adiabatic deceleration resulting from the interplay of scattering and focusing, and solar wind convection (Kocharov et al 1998;Vainio et al 2000).…”
Section: Interplanetary Transport Modelmentioning
confidence: 99%
“…We infer the interplanetary transport conditions and the injection time profile at the Sun from a set of in-situ measured sectored intensities by using the inversion technique presented in Agueda et al (2008) and Agueda et al (2009b). By taking the angular response of the sectors scanned by the LEFS60 telescope into account, it is possible to transform the simulated PADs into sectored intensities measured by the telescope (Agueda et al 2008).…”
Section: Fitting Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…This equation may take additional effects into account that arise, for example, from the spatial variation in the guiding magnetic field. A lot of work has been done in simulating this transport by numerically solving Fokker-Planck equations that include different effects, such as adiabatic focusing, adiabatic cooling or perpendicular diffusion, assuming different types of magnetic turbulence that lead to different shapes of the diffusion coefficients (for review see Dröge & Kartavykh 2009;Dröge et al 2010;Dröge 2003;Agueda et al 2008;Qin et al 2004;Ruffolo 1995).…”
Section: Introductionmentioning
confidence: 99%